Lacustrine turbidites as a tool for quantitative earthquake reconstruction: New evidence for a variable rupture mode in south central Chile. Issue 3 (21st March 2014) - Moernaut, Jasper; Daele, Maarten Van; Heirman, Katrien; Fontijn, Karen; Strasser, Michael; Pino, Mario; Urrutia, Roberto; De Batist, Marc
Abstract Understanding the long‐term earthquake recurrence pattern at subduction zones requires continuous paleoseismic records with excellent temporal and spatial resolution and stable threshold conditions. South central Chilean lakes are typically characterized by laminated sediments providing a quasi‐annual resolution. Our sedimentary data show that lacustrine turbidite sequences accurately reflect the historical record of large interplate earthquakes (among others the 2010 and 1960 events). Furthermore, we found that a turbidite's spatial extent and thickness are a function of the local seismic intensity and can be used for reconstructing paleo‐intensities. Consequently, our multilake turbidite record aids in pinpointing magnitudes, rupture locations, and extent of past subduction earthquakes in south central Chile. Comparison of the lacustrine turbidite records with historical reports, a paleotsunami/subsidence record, and a marine megaturbidite record demonstrates that the Valdivia Segment is characterized by a variable rupture mode over the last 900 years including (i) full ruptures (Mw ~9.5: 1960, 1575, 1319 ± 9, 1127 ± 44), (ii) ruptures covering half of the Valdivia Segment (Mw ~9: 1837), and (iii) partial ruptures of much smaller coseismic slip and extent (Mw ~7.5–8: 1737, 1466 ± 4). Also, distant or smaller local earthquakes can leave a specific sedimentary imprint which may resolve subtle differences in seismic intensity values. For instance, the 2010 event at the Maule Segment produced higher seismic intensities toward southeastern localities compared to previous megathrust ruptures of similar size and extent near Concepciόn.